Internalisasi Nilai-Nilai Agama Islam dalam Membentuk Anak Usia Dini yang Berkarakter Di TK Atthoyyibatul Islamiyah Tegaldlimo – Banyuwangi - Habibah, Nur Faiz (Jurnal Munaqasyah, 2019)
Abstract: One of them is Tegaldlimo Banyuwangi TK At Toyyibatul Islamiyah educational institution which has succeeded in gaining public trust in the formation of children's character. Various programs of the kindergarten At Thoyyibatul Islamiyah educational institutions are very supportive towards the formation of children's character by internalizing the values ​​of Islam in depth. For example children are introduced to the holidays of Islam and at the same time celebrate with selametan events which also involve the role of parents. Besides that they are also accustomed to pray in every activity carried out. Like prayer when learning will begin accompanied by prayer and prayer when going in and out of class. The school also cooperates with parents to internalize religious values ​​early so that children are accustomed and firmly planted until someday and anytime. Good religious values ​​related to faith, morals and worship. From some of the descriptions above, this study discusses how to internalize the values ​​of Islamic religion in shaping early childhood with character in TK At Thoyyibatul Islamiyah with conclusions. From some of the descriptions above it can be concluded that the internalization of Islamic values ​​to form early childhood character Atthoyyibatul Islamiyah kindergarten can be carried out with various strategies carried out by the teacher including strategies with exemplary, habitual, wise advice, by giving attention and punishment. The five strategies are carried out so that students have a quality character in terms of worship, behavior and socialization.